2015
DOI: 10.1039/c5ra06847a
|View full text |Cite
|
Sign up to set email alerts
|

Core double–shell cobalt/graphene/polystyrene magnetic nanocomposites synthesized by in situ sonochemical polymerization

Abstract: Core double-shell cobalt/graphene//polystyrene nanocomposites (Co/C//PS) were synthesized by in situ sonochemical polymerization technique. Commercial Co/C nanoparticles are used and successfully lead to gram-scale production of processable nanocomposite. Synthesized Co/C//PS nanocomposites result in homogeneous and dense dispersion of particles with or without additional polymeric matrix. They showed improved thermal properties such as higher initial degradation temperatures and a significant increase of glas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…When the UV exposure time increased to 120 min (i) an increase in absorbance of the IR bands with maxima at 837, 1244 and 1273 cm −1 ; (ii) a change of the ratio between the absorbance of the IR bands peaked at 1450 and 837 cm -1 from 5 to 1.7; (iii) an up-shift of the IR band from 1743 cm −1 to 1747 cm −1 ; and (iv) the appearance of a new IR band at 1701 cm −1 were observed. This IR band is situated close to the IR band at 1683 cm −1 , reported to be assigned to the vibrational mode C=C stretching of the styrene vinyl group [28]. In our opinion, these variations support the appearance of the amorphous portions of PS and the modification of the GO sheets covalently grafted with BPO.…”
Section: Photoluminescence Of the Ps Microspheres And Their Compositesupporting
confidence: 72%
“…When the UV exposure time increased to 120 min (i) an increase in absorbance of the IR bands with maxima at 837, 1244 and 1273 cm −1 ; (ii) a change of the ratio between the absorbance of the IR bands peaked at 1450 and 837 cm -1 from 5 to 1.7; (iii) an up-shift of the IR band from 1743 cm −1 to 1747 cm −1 ; and (iv) the appearance of a new IR band at 1701 cm −1 were observed. This IR band is situated close to the IR band at 1683 cm −1 , reported to be assigned to the vibrational mode C=C stretching of the styrene vinyl group [28]. In our opinion, these variations support the appearance of the amorphous portions of PS and the modification of the GO sheets covalently grafted with BPO.…”
Section: Photoluminescence Of the Ps Microspheres And Their Compositesupporting
confidence: 72%
“…The medium-to-very broad band observed between 3400 and 2700 cm À1 indicated the presence of -OH stretch. [48][49][50] The peaks observed for the cell-free medium match with those of standard PAA (Fig. 5b).…”
Section: Resultssupporting
confidence: 55%
“…Complementary observations backed with Raman analysis revealed that graphene is much thinner and partially transformed into amorphous carbon (Herman et al 2015 ). Also traces of oxidized cobalt were detected by Raman spectroscopy (Herman et al 2015 ). Thus, scheme 2 is more critical.…”
Section: Resultsmentioning
confidence: 92%
“…Scheme 2 is the radical option aimed to improve dispersion and cohesion. It is detailed elsewhere (Herman et al 2015 ). For practical reasons, m i was limited to 100 mg.…”
Section: Methodsmentioning
confidence: 99%